Analysis of Population Density, Economic Growth Rate, and the Number of Motorized Vehicles on Environmental Qual-ity in Indonesia - Intan Angelisa; M. Ridwansyah; Jaya Kusuma Edi; Zainul Bahri (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
This study, entitled "A nalysis of Population Density, Economic Growth Rate, and the Number of Motorized Vehicles on Environmental Quality in Indonesia," aims to analyze: 1) the development of environmental quality in Indonesia; 2) the influence of population density, economic growth rate, and the number of motorized vehicles on environmental quality in Indonesia. This study employed a quantitative method, utilizing secondary data from 2019-2023, sourced from the Central Statistics Agency (BPS), the Ministry of Environment and Forestry (KLHK), and other sources. Panel data analysis tools, classical assumption tests, and hypothesis testing were used. Panel data regression results indicate that, partially, population density has a significant negative effect, economic growth rate has a negative and significant effect, while four-wheeled and two-wheeled motorized vehicles have a positive and significant effect on environmental quality in Indonesia. Meanwhile, collectively, population density, economic growth rate, and the number of motorized vehicles significantly influence environmental quality in Indonesia.